Characterisation of screen-printed gold and gold nanoparticle-modified carbon sensors by electrochemical impedance spectroscopy - Bernalte, Elena (2013)
Gold-based screen-printed electrodes have been characterised by electrochemical impedance spectroscopy (EIS) to better understand their behaviour in electroanalytical applications, particularly in the anodic stripping voltammetry of Hg(II). After a first exploration by cyclic voltammetry, impedance spectra of gold-based screen-printed sensors were recorded in 0.1 M HCl electrolyte solution, in the presence of dissolved oxygen and with no electrochemical pre-treatment of the surface. The spectra demonstrated the differences in the interfacial characteristics of each kind of sensor. Structural changes in the surface of SPGEs caused by amalgam formation in the presence of Hg(II) were investigated by EIS. The results obtained were used to elucidate the implications for using the sensor in the stripping voltammetric determination of Hg(II) in environmental samples.